RELATIONSHIP OF FEMALE AGE AND SPERM QUALITY WITH THE SUCCESSFUL OF IUI LITERATURE REVIEW - Dhea Hesty Purwaningrum; Sri Ratna Dwiningsih; Sulistiawati Sulistiawati (Universitas Airlangga, 2021)
Abstract Background: Infertility in developing countries is higher at 30% compared to developed countries at 5-8%. The factors that influence infertility are maternal (women) age and sperm factors. Therapy in handling infertility in the form of Assisted Reproductive Technology (ART) with one of them is Intrauterine Insemination (IUI). The success rate of IUI is the percentage of IUI programs that give results as desired depending on the type of calculation used such as pregnancy rate or live birth rate. Method: This research is a literature review. The research question with PICO standard is "What is relationship between woman's age and sperm quality with the success of Intrauterine Insemination?". 70 literatures were obtained from Cochrane, Sciencedirect, PubMed, and google scholar databases. Literature screening was done by looking at the inclusion and exclusion criteria that have been set, so that 7 literature will be reviewed.  Results: From all the literature on the relationship of woman's age with the pregnancy rate in the IUI process stated that there was a significant relationship between the age of the woman with the success of IUI. Most of literature (75%) on the relationship of sperm quality with pregnancy rates in the IUI process states that there is a relationship between sperm quality and the success of IUI. The percentage of pregnancies in the IUI program can reach more than 10% with a sperm concentration >10x106/ml. Conclusion: From a review of 7 literature, the age of women who are ideal for IUI is 20-35 years with a pregnancy of  20%. In a sperm concentration >10x106/ml and sperm morphology ≥ 5% can get >10% pregnancy rate, and a pregnancy rate of >8% on sperm motility ≥ 75%.